2020
DOI: 10.1016/j.crphys.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pain responses, hemodynamic reactivity and fibre type composition between Bergström and microbiopsy skeletal muscle biopsies

Abstract: This study tested the hypotheses that 1) skeletal muscle biopsies performed with the Bergström needle evoke larger perceptions of pain and greater hemodynamic reactivity compared to biopsies performed with the microbiopsy needle, and 2) both needles yield samples with similar fibre type compositions when samples are collected at similar skeletal muscle depths. Fourteen healthy (age: 21.6 ± 3.2 years; VO 2 peak: 41.5 ± 5.8 mL/kg/min) males (n = 7) and females (n = 7) provided two resting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…It has been suggested that as few as 50 fibers ( McCall et al, 1998 ) is necessary to accurately characterize the sample collected, but depending on the specific fiber type, the need to harvest up to 200 fibers has been reported ( McGuigan et al, 2002 ). Townsend et al (2016) analyzed ∼150 fibers on average in young males using the microbiopsy in a pilot study, but fiber yield is unclear for other studies using this technique ( Hughes et al, 2015 ; Bonafiglia et al, 2020 ). We were able to analyze a few hundred fibers (>500) per microbiopsy sample in a young and older cohort, and a yield of several hundred fibers was possible by combining data from multiple cross-sections of tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that as few as 50 fibers ( McCall et al, 1998 ) is necessary to accurately characterize the sample collected, but depending on the specific fiber type, the need to harvest up to 200 fibers has been reported ( McGuigan et al, 2002 ). Townsend et al (2016) analyzed ∼150 fibers on average in young males using the microbiopsy in a pilot study, but fiber yield is unclear for other studies using this technique ( Hughes et al, 2015 ; Bonafiglia et al, 2020 ). We were able to analyze a few hundred fibers (>500) per microbiopsy sample in a young and older cohort, and a yield of several hundred fibers was possible by combining data from multiple cross-sections of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiopsy is an appealing alternative to the Bergström given its smaller needle diameter and decreased level of invasiveness. Indeed, subjects report less pain and a preference for the microbiopsy technique compared to the Bergström ( Hayot et al, 2005 ; Bonafiglia et al, 2020 ). Despite its increasing popularity, there is a paucity of work using the microbiopsy for histological analyses, which is at least partially owed to hesitation regarding the smaller tissue sample reported to range from 14 to 22 mg ( Hayot et al, 2005 ; Hughes et al, 2015 ; Townsend et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the small muscle biopsy sample—when compared to the Bergstrom technique—the percutaneous biopsy technique is not useful for comprehensive histological and molecular assessment. Despite being perceived as less painful compared to the Bergstrom technique (Bonafiglia et al, 2020 ), continued use of the percutaneous muscle biopsy technique should be met with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, percutaneous microbiopsy needles have been used as an alternative to the Bergstrom needle for obtaining human skeletal muscle biopsy (Hughes et al, 2015 ). Although the microbiopsy technique results in the extraction of a smaller piece of muscle tissue than the Bergstrom needle, it does not require a pre‐biopsy incision of the skin, involves a lower gauge needle and is perceived as being less invasive and painful than the Bergstrom technique (Bonafiglia et al, 2020 ; Hughes et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…All three whole‐body aerobic outcomes were assessed during incremental step tests to exhaustion before and after training: V̇O2peak was calculated as the highest 30 s average oxygen consumption (collected via gas exchange using a metabolic cart), WR peak was calculated as the highest 30 s average work rate, and OBLA was determined as the work rate during when blood lactate levels exceeded 4.0 mmol/l. Using the Bergström skeletal muscle biopsy technique as previously described (Bonafiglia et al, 2020), vastus lateralis biopsies were collected from the REL and CTRL groups only. Biopsies were collected after an overnight fast (∼12 h) before (pre) and ∼72 h (post) following the final REL session or the end of the no‐exercise control intervention.…”
Section: Methodsmentioning
confidence: 99%